The great American songbook celebrating 100 years of music in America - Carmichael, Hoagy 1899-1981; Astaire, Fred 1899-1987; Garland, Judy 1922-1969 (Turner Entertainment Co. [u.a.], 2010)
Popular entertainer Michael Feinstein hosts a documentary on the evolution of American popular music, told through stories of the greatest songwriters of all time. Includes Irving Berlin, Cole Porter, George and Ira Gershwin, Arthur Freed and Fats Waller. Also includes rare performance footage of singers Bessie Smith, Hoagy Carmichael, Judy Garland, and dancers Fred Astaire and Ginger Rogers
Enth. Bonusmaterial: Audio commentary by Michael Feinstein. Vintage musical short "A new romance of celluloid: we must have music"